2008
DOI: 10.1212/01.wnl.0000326895.58992.27
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin use leads to larger intracerebral hematomas

Abstract: Background Among patients with intracerebral hemorrhage (ICH) warfarin use prior to onset leads to greater mortality. In a retrospective study we sought to determine if warfarin use is associated with larger initial hematoma volume, one determinant of mortality after ICH. Methods We identified all patients hospitalized with ICH in the Greater Cincinnati region from 1/05–12/05. ICH volumes were measured on the first available brain scan using the abc/2 method. Univariable analyses and a multivariable generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(171 citation statements)
references
References 27 publications
(28 reference statements)
13
150
3
5
Order By: Relevance
“…21 When warfarin-related intracerebral hemorrhage occurs, stroke mortality rate doubles in a dose-dependent manner, 22 likely related to the large size of hematoma. 23 Thus, preventing hemorrhagic cerebrovascular events is of paramount importance for those patients who require anticoagulation because of high risk of recurrent embolic stroke. In this analysis, patients with previous IS/TIA randomized to HDER experienced similar protection from arterial thromboembolism and death when compared with well-managed warfarin (median time-in-therapeutic range 68.4%) and superior protection from primary hemorrhagic stroke and ICH, similar to the overall ENGAGE AF-TIMI 48 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…21 When warfarin-related intracerebral hemorrhage occurs, stroke mortality rate doubles in a dose-dependent manner, 22 likely related to the large size of hematoma. 23 Thus, preventing hemorrhagic cerebrovascular events is of paramount importance for those patients who require anticoagulation because of high risk of recurrent embolic stroke. In this analysis, patients with previous IS/TIA randomized to HDER experienced similar protection from arterial thromboembolism and death when compared with well-managed warfarin (median time-in-therapeutic range 68.4%) and superior protection from primary hemorrhagic stroke and ICH, similar to the overall ENGAGE AF-TIMI 48 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The apolipoprotein E ε2 allele is associated with larger hematomas, which appears to explain its effect on outcome [15]. The relation between oral anticoagulation use and baseline hematoma volume is unclear; some studies have shown increased baseline volumes [16,17], whereas others have not [15,18].…”
Section: Initial Hematomamentioning
confidence: 99%
“…The observed increase is most likely due to the increased use of warfarin by patients with atrial fibrillation [58]. The use of warfarin at the time of ICH is associated with hematoma expansion [16,18] and increased mortality [15][16][17]59].…”
Section: Anticoagulation Reversalmentioning
confidence: 99%
“…Individuals on warfarin with an international normalized ratio >3 have an increased risk for having larger hematomas [146]. To be able to potentially curtail the hematoma growth of different agents, including vitamin K (either with or without fresh frozen plasma), factor VII, and prothrombin complex concentrates have been used.…”
Section: Management Of Ich In Patients On Concurrent Antithrombotic Tmentioning
confidence: 99%